The Efficacy and Safety of Acupuncture for Prophylaxis of Vestibular Migraine: A Study Protocol for a Randomized Controlled Trial - Hu, Tianye; Hu, Hantong; Chen, Feng; Jiang, Bin; Shen, Fengfei; Su, Yingying; Yang, Mengyi; Hu, Jin (Frontiers in Neurology, 2021)
Introduction: With a high incidence rate and low diagnosis rate, vestibular migraine (VM) can seriously affect the quality of life of patients, but it remains difficult to manage by current treatment options. Acupuncture may be a potential treatment option for VM prophylaxis, but the currently available evidence is still uncertain. Therefore, this trial aims to evaluate the efficacy and safety of acupuncture for VM prophylaxis. Methods: This is a 28-week parallel, randomized, controlled clinical trial including 4 weeks of baseline, 8 weeks of treatment, and 16 weeks of follow-up. A total of 72 participants will be randomly assigned to two groups. The participants will receive acupuncture in the experimental group, while the participants in the control group will be treated with venlafaxine. The primary outcome measures are change in vertigo/migraine days and vertigo/migraine attacks, vertigo severity, and migraine intensity per 4 weeks from baseline. The secondary outcome measures are change in doses of rescue medication, anxiety level, depression level, and quality of life per 4 weeks from baseline. Adverse events will be recorded for safety evaluation. Discussion: This study will investigate the efficacy and safety of acupuncture for VM prophylaxis. The results will contribute to determining whether acupuncture can serve as an optional treatment strategy for treating VM. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT0464088.